The Vertical Profile Of Nitrate in Pinang Dalam Oxbow Lake Buluh China Village Siak Hulu Sub District Kampar District Riau Province - Muhammad Zaki; Madju Siagian; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research has been done in Pinang Dalam Oxbow Lake from Maret 2014. Thisresearch aims to understand the vertical profile of nitrate in Pinang Dalam oxbow lake. Theresearch used survey method. Sample were taken in three stations, namely station 1, station 2 andstation 3. Sampling vertical based transparency, at surface, 2,5 secchi disk, and in the bottom.The parameters of water quality measured nitrate, phosphate, temperature, transparancy, depth,pH, free carbon dioxide (CO) and dissolved oxygen (DO). The result shown nitrate range 0,020- 0,337 mg/L, phosphate 0,037 – 0,710 mg/L, temperature 28,3-28,7 oC, transparancy 27,3-28,5cm, depth 145-302 cm, pH 5, free carbon dioxide 5,33 - 9,32 mg/L, and dissolved oxygen 2,40- 6,83 mg/L. The vertical profile of nitrate showed increased with the increment of depth. Theparameters of water quality were observed still support the aquatic organisms.Keywords : nitrate, the vertical profile, Pinang Dalam Oxbow